Effects of visual training in tennis performance in male junior tennis players: a randomized controlled trial - Bonato, M.; Gatti, C.; Rossi, C.; Merati, G.; La Torre, A. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Tennis is an open-skill dynamic sport in which players over a limited period of time have to process and integrate complex visual information. Therefore, the aim of this study was to assess the effects of 12 weeks visual training (VT) in junior tennis players. METHODS: This was a two-arm parallel-group randomized-controlled trial in which 20 male junior players were randomized to either an experimental group (EG: N.=10; age: 15±1 year; height: 1.67±0.01 m; body mass: 52±11 kg) that performed VT or a control group (CG: N.=10; age: 15±1 year; height: 1.70±0.01 m; body mass: 52±12 kg) that was involved in a standard training for 3 sessions a week for 12 weeks. Players were tested at baseline (T0) and after 12 weeks of training (T12) for evaluate sweet spot, speed and time course between split steep and shoulder rotation during forehand, backhand, 1st and 2nd serve and return to serve. RESULTS: At T12 two-way Anova with Tuckey multiple comparison test showed significant improvements in sweet spot (P=0.032; ES: 2.1±0.3, most likely) and speed (P=0.002; ES: 1.8±0.4, very likely) during second serve were found. Moreover, the time course between the split step and shoulder rotation in forehand (P=0.0008; ES: =2.0±0.3, most likely), backhand (P=0.001; ES: =2.0±0.5, most likely), and return to serve (P=0.001; ES: 1.7±0.2, very likely) improved significantly. CONCLUSIONS: These results suggest that VT was effective to improve on-court tennis performance in junior tennis players.